Perancangan Ide Bisnis "Little Learners" Flashcards - Jesslyn Faustina; Hutomo Setia Budi (Jurnal Vicidi, 2017)
This study focuses on the relationship between visual communication design and entrepreneurship, which aims to generate a solution for the educational issue in children aged 3 to 5 caused by over- attachment to mobile devices (Radesky & Schumacher, 2014), through designing a business concept. Research was conducted with qualitative methods, including interviews with three professionals in the field of early education, a group play observation of 5 children aged 4 and 5, supported by literature review from related journals, books, and online articles. Research and analysis produced the business concept “Little Learners” Flashcards, a learning aid in the form of flashcards with various activities to do for children aged 3 to 5. This study concludes that “Little Learners” Flashcards can be an effective solution, due to the fact that flashcards exercise different skills such as motor, visual, and verbal skills, and at the same time encouraging children to be more engaged. Moreover, flashcards can help parents be more involved and interactive with their children. Based on positive responses from the research, this business looks prospective. The sustainability of this business is also guaranteed, seeing as there are countless educational materials that are yet to be explored and represented in flashcard form.